Mario Vargas Llosa: “La literatura es fuego”. Una aproximación - Morales Mena, Javier (2019)
The article proposes a reading of the essay "Literature is fire". A synthesis of the main approaches that have been made on the trials of Mario Vargas LLosa is made. The balance allows to warn that no analysis of the structural components that organize the essay have been carried out. In this way, Emphasis is placed on the explanation of the narrative and rhetorical resources used by the essayist when representing the author, literature and tensions with society.